A Logic Circuit Simulation for Finding Identical or Redundant Files using Counter and Register - Rompis, Lianly (European Journal of Applied Sciences, 2018)
Computers and internet have become globally used nowadays and also part of the important facilities that could support information exchanges and cloud computing. People deals with texts, images, and videos processing, reaches out the specific goal of their works. It happens that due to much information and procedures, people will have many redundant files such as images or videos in their host computers or terminals, or maybe for some specific reasons people need to find data from big servers that surely have many files with same type and property because people accidentally put them there without knowing others also probably put the same ones. Using the basic concept of sequential logic circuit and electronic workbench 5.12 software, a logic circuit simulation consists of counter and register could be designed to show logically how to a computer or digital machine would interact to find redundant files, images or videos, or same files from many identical data from a server. The methods being used are study literature, analysis, design, and simulation. The output shows an expected result, a logic circuit simulation that could be applied on digital devices for finding identical or redundant files, or other related important process.